GAMBARAN GAYA HIDUP DAN POLA KONSUMSI MAKANAN SERTA STATUS GIZI PADA SUPIR BUS MINI CV. SBI (SIBULUAN INDAH) DAN CV. FLORES TRAYEK MEDAN-SIBOLGA TAHUN 2016 - Dahlia Ningsih Panggabean; Etti Sudaryati; Evawany Y Aritonang (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
Developments in technology and industry has brought many changes in behavior include changes in lifestyle (smoking, drinking coffee and tea, and physical activity) and food consumption patterns. The bus driver is a group of people who require nutritional status and health conditions are optimal in order to carry out their work. Nutrition workers have an important role, both for the well-being and in order to improve discipline and productivity. This research a descriptive study using survey methods to describe the lifestyles and patterns of food consumption and nutritional status of the bus driver mini CV. SBI (Sibuluan Beautiful) and CV. Flores route Medan-Sibolga 2016. Total sample of 66 people. The data collection by using the from method of 24 hours food recall and food frequency. From the research, it known that the lifestyle of a bus driver among other habit of smoking category (80.3%) and the number of cigarettes smoked per day were considered moderate smokers (48.5%.), drinking coffee (86.4%) and category drinking tea (95.5%), a bus driver who drink coffee and tea on average three cups per day (37.9%) and (39.4%), and physical activity bus driver classified in moderate activity (43.9% ). The level of energy consumption categorized as very high (50%), the level of protein consumption is categorized as very high (39.4%), while the rate of fat consumption categorized as high (54.5%). Based on the research results suggested to the bus driver for more attention to lifestyle (smoking, drinking coffee and tea, and physical activity) and eating foods that are nutritionally balanced according to the needs or the intake body Keywords: lifestyle, food consumption patterns, nutritional status, the bus driver.